Periorbital eruptive vellus hair cysts: a challenging treatment in an atypical location - Bruna dos Anjos Bortolini; Rafael Cavanellas Fraga; Paulo Sergio Emerich Nogueira; Tiago de Almeida Grippa; Vitor Angelo Ferreira (Surgical & Cosmetic Dermatology)
Eruptive vellus hair cyst is a rare condition resulting from the abnormal development of vellus hair follicles, leading to the formation of multiple follicular papules. While it can appear on the face, only five cases specifically located in the periorbital region have been described in the literature. Its treatment is challenging, particularly in the case we report here due to the peculiar location of the lesions, which increases the risk of postoperative scarring and dyschromia. We present a report that addresses the challenging diagnosis and successful treatment of a rare case of eruptive vellus hair cyst located in the periorbital region.